'Avarice and Rapacity' and 'Treasonable Correspondence' in 'an Emporium for All the World': The British capture of St Eustatius, 1781. Issue 3 (3rd July 2018) - Cock, Randolph
Abstract : In the Revolutionary War the American rebels relied on supplies of munitions, especially gunpowder, from Europe. To circumvent the embargo and avoid seizure by the British, many of those supplies were routed through the neutral Dutch West Indian island of St Eustatius. To cut off supplies to the Americans, the British invaded and occupied that island. But the trade simply switched to Danish islands, while the British naval and military commanders, Admiral Rodney and General Vaughan, became deeply embroiled in litigation over the illegal seizure and sale of trade goods belonging to the island's merchants.